2020
DOI: 10.1002/lary.28632
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Facial Nerve Stimulation After Cochlear Implantation in Adult and Pediatric Recipients

Abstract: Objectives/Hypothesis Facial nerve stimulation (FNS) can occur after cochlear implantation for a small number of recipients. This study aimed to investigate if a correlation exists between the variables involved in FNS. Study Design Retrospective cohort review. Methods There were 32 out of 1,100 cochlear implant recipients who experienced FNS in our clinic between 2010 and 2019. The following variables were recorded from a retrospective chart review: grade of FNS, onset of FNS, the number of channels stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
8
2
1
Order By: Relevance
“…In our study, in six patients, FNS occurred later. In the few studies describing Late‐FNS, it was suggested that progression of otosclerosis with changes of tissue impedance and/or erosion of the thin bony layer between the scala tympani and the facial nerve was greater than in patients without otosclerosis 27,28 . Surprisingly, in our study, all the six patients with Late‐FNS already had extensive otosclerotic lesions on preoperative CT‐scan.…”
Section: Discussioncontrasting
confidence: 62%
“…In our study, in six patients, FNS occurred later. In the few studies describing Late‐FNS, it was suggested that progression of otosclerosis with changes of tissue impedance and/or erosion of the thin bony layer between the scala tympani and the facial nerve was greater than in patients without otosclerosis 27,28 . Surprisingly, in our study, all the six patients with Late‐FNS already had extensive otosclerotic lesions on preoperative CT‐scan.…”
Section: Discussioncontrasting
confidence: 62%
“…We found FNS in at least one recording in all of our 26 animals and in 178 of 393 recordings. This represents a high incidence (45%) compared to about 10% that was usually reported in human CI users [5,9,13,24,29]. The first potential underlying cause of this difference is related to the species: The anatomy of the inner ear and facial nerve (FN) is different in guinea pigs and humans.…”
Section: Overall Minmentioning
confidence: 99%
“…FNS may occur directly after CI activation, but sometimes starts with a time delay of up to several years of CI usage [7,9]. The FNS is due to the anatomical proximity of the intrascalar CI contacts to the facial nerve (FN), a proximity that allows the current to reach the FN.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, facial nerve stimulation from a CI ranges between 0.9 and 15%. [59][60][61] Altered taste is another potential complication after CI implant surgery. It results when the chorda tympani nerve is disturbed during surgery.…”
Section: Infectious Complicationsmentioning
confidence: 99%